Synthesis of [Fe(L)(bipy)]n spin crossover nanoparticles using blockcopolymer micelles. Issue 45 (7th November 2016) - Klimm, Ottokar; Göbel, Christoph; Rosenfeldt, Sabine; Puchtler, Florian; Miyajima, Nobuyoshi; Marquardt, Katharina; Drechsler, Markus; Breu, Josef; Förster, Stephan; Weber, Birgit
Abstract : Blockcopolymer micelles prove to be ideal templates for the synthesis of coordination polymer nanoparticles with tunable crystallinity. Abstract : Nowadays there is a high demand for specialized functional materials for specific applications in sensors or biomedicine ( e.g. fMRI). For their implementation in devices, nanostructuring and integration in a composite matrix are indispensable. Spin crossover complexes are a highly promising family of switchable materials where the switching process can be triggered by various external stimuli. In this work, the synthesis of nanoparticles of the spin crossover iron(ii ) coordination polymer [Fe(L)(bipy)] n (with L = 1, 2-phenylenebis(iminomethylidyne)bis(2, 4-pentanedionato)(2-) and bipy = 4, 4′-bipyridine) is described using polystyrene-poly-4-vinylprididine blockcopolymer micelles as the template defining the final size of the nanoparticle core. A control of the spin crossover properties can be achieved by precise tuning of the crystallinity of the coordination polymer via successive addition of the starting material Fe(L) and bipy. By this we were able to synthesize nanoparticles with a core size of 49 nm and a thermal hysteresis loop width of 8 K. This is, to the best of our knowledge, a completely new approach for the synthesis of nanoparticles of coordination polymers and should be easily transferable to other coordination polymers and networks. Furthermore, the use of blockcopolymers allows a further functionalization of the obtained nanoparticles by variation of the polymer blocks and an easy deposition of the composite material on surfaces via spin coating.